Heroes in Dark Times (Sanctorum. Scritture, pratiche, immagini, 2023)
In the accounts of disaster of the early modern period, it seemed as though the heroes were missing, replaced by the anthropomorphic rage of the natural elements. Nevertheless, it did sometimes happen that singular figures emerged from the blurry mass of the people and their dramatic anecdotes, and sprang into action to address the emergency. Sometimes they were saints, sometimes local institutions: the former were invoked to mediate with heaven to placate divine anger through miracles, and the latter to manage the catastrophe and provide aid and relief.